Four new genome sequences of the Pallas’s cat (Otocolobus manul): an insight into the patterns of within-species variability - Bubenikova, Jana; Plasil, Martin; Burger, Pamela A.; Horin, Petr (Frontiers in Genetics, 2024)
Manul (Otocolobus manul) is the only representative of the genus Otocolobus, which makes up the Leopard Cat lineage along with the genus Prionailurus. Their habitat is characterized by harsh environmental conditions. Although their populations are probably more stable than previously thought, it is still the case that their population size is declining. Conservation programs exist to protect manuls, but those based on captive breeding are often unsuccessful due to their increased susceptibility to diseases. The manul is therefore a suitable model species for evolutionary and diversity studies as well as for studying mechanisms of adaptation to harsh environment and mechanisms of susceptibility to diseases. Recently, the genome of the O. manul based on nanopore long-range sequencing has been published. Aiming to better understand inter- and intraspecific variation of the species, we obtained information on genome sequences of four other manuls, based on whole genome resequencing via the Illumina platform. On average, we detected a total of 3,636,571 polymorphic variants. Information on different types of structural variants and on the extent of SNP homozygosity, not available from the reference genome, was retrieved. The average whole-genome heterozygosity was almost identical to that found in the O. manul reference genome. In this context, we performed a more detailed analysis of the candidate gene EPAS1 potentially related to adaptation to the hypoxic environment. This analysis revealed both inter- and intraspecific variation, confirmed the presence of a previously described non-synonymous substitution in exon 15 unique to manuls and identified three additional unique non-synonymous substitutions located in so far not analyzed EPAS1 exonic sequences. The analysis of lncRNA located in the intron 7 of EPAS1 revealed interspecific variability and monomorphic nature of the sequence among analyzed manuls. The data obtained will allow more detailed analyses of the manul genome, focusing on genes and pathways involved in their adaptation to the environment and in susceptibility to diseases. This information can be helpful for optimizing conservation programs for this understudied species.